The right to privacy and the protection of personal data across borders - Robles Osollo, Ana Gloria (Universidad Nacional del Litoral, 2021)
The right to privacy and the transnational personal data, urge the legal systems for and adequate protection, the information exchange between countries, such as health, politics, trade and the use of new technologies, as well as the possible collision with the right of access to information. The analysis of the European regulations to protect data, as well as the reception of Mexican regulations as a leading Latin American country and a signatory of the Convention 108 of Strasbourg is paramount.